2004
DOI: 10.1021/jf049097p
|View full text |Cite
|
Sign up to set email alerts
|

Novel Approach for Food Safety Evaluation. Results of a Pilot Experiment To Evaluate Organic and Conventional Foods

Abstract: There is evidence that organic food often contains relatively high amounts of natural toxic compounds produced by fungi or plants, whereas corresponding conventional food tends to contain more synthetic toxins such as pesticide residues, but only a few studies have evaluated the impact of their consumption on health. This study proposes a novel approach to evaluate the potential health risk of organic compared to conventional food consumption, that is, the assay of sensitive markers of cell function in vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 38 publications
2
45
0
Order By: Relevance
“…1,18 No systematic nutrition-related health effects have been established either; however, some studies have shown that immunological parameters and growth might be sensitive to effects from cultivation systems. 14,21,22,42 Cultivation Methods Effect on Nutritional Quality and Health Biomarkers. The rats used in the current study were all clinically healthy, with normal food intake and increase in body weight during the long-term feeding experiment without any remarkable deviations from a "normal physiological response".…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,18 No systematic nutrition-related health effects have been established either; however, some studies have shown that immunological parameters and growth might be sensitive to effects from cultivation systems. 14,21,22,42 Cultivation Methods Effect on Nutritional Quality and Health Biomarkers. The rats used in the current study were all clinically healthy, with normal food intake and increase in body weight during the long-term feeding experiment without any remarkable deviations from a "normal physiological response".…”
Section: ■ Discussionmentioning
confidence: 99%
“…A study by Finamore et al 22 observed a difference in lymphocyte function in rats due to cultivation system.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most focus has been given to the growth and reproduction of animals, and found no consistent effects 4 and the results from the oldest studies are unlikely to be relevant for modern farming practices. 7 One recent study of rats fed conventional or organic wheat showed increased lymphocyte function in the organic treatment, 19 but the model used had little relevance for most human consumers of organic food.…”
Section: Introductionmentioning
confidence: 99%
“…Major reasons are the care for animals, the environment, but also the potential benefits for the health of the consumer (Finamore et al, 2004;Rembialkowska, 2007;Givens et al, 2008). A large number of studies (Rembialkowska, 2007;Baker et al, 2002;Jestoi et al, 2004;Hoogenboom et al, 2008) have addressed the latter issue, focusing e.g.…”
Section: Introductionmentioning
confidence: 99%